NIH3T3 Directs Memory-Fated CTL Programming and Represses High Expression of PD-1 on Antitumor CTLs - Qin, Yingyu; Lee, Yuna; Seo, Jaeho; Kim, Taehyun; Shin, Jung Hoon; Park, Se-Ho (Frontiers in Immunology, 2019)
Memory CD8+ T cells have long been considered a promising population for adoptive cell therapy (ACT) due to their long-term persistence and robust re-stimulatory response. NIH3T3 is an immortalized mouse embryonic fibroblast cell line. We report that NIH3T3-conditioned medium (CM) augments effector functions of CTLs following antigen priming, as well as conferring phenotypic and transcriptional properties of central memory cells. Infusion of NIH3T3-CM-educated CTLs into naïve mice demonstrated that they predominantly developed to central memory cells. A large number of NIH3T3-CM-educated CTLs with high functionality persisted and infiltrated to the tumor mass. In addition, NIH3T3-CM inhibited CTLs expression of PD-1 and programmed them to resist against high expression of PD-1. Consequently, established tumor models showed that infusion of NIH3T3-CM-educated CTLs dramatically improves antitumor immunity. Most importantly, NIH3T3-CM also promoted human CD8+ T cells differentiation into memory cells, which suggested that NIH3T3-CM-programmed CTLs are good candidates for adoptive transfer in tumor therapy.